RELATIONSHIPS ON ABILITY TO DRAW SHAPES AND SKETCHES WITH STUDENTS EXPRESSIVE DRAWING - Grand Alvian Naibaho; Sugito Sugito (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2021)
This study aims to prove whether there is a significant relationship, the amount of contribution (contribution), and to see the size of the relationship between the ability to draw shapes and sketches with the ability to draw expressive in class X SMA Bangun Insan Mandiri Medan. The method used in this research is correlational research, which is to see the relationship between the two independent variables and the dependent variable. The population in this study were students of class X SMA Bina Insam Mandiri Medan for the 2019/2020 academic year, totaling 32 students. Based on the results of research and discussion, it can be concluded that there is a relationship between the ability to draw shapes and draw sketches simultaneously on the expressive drawing ability of class X students of SMA Bangun Insan Mandiri Medan. Partially there is a relationship between the ability to draw shapes and the expressive drawing ability of class X SMA Bangun Insan Mandiri Medan, Partially there is a relationship between drawing a sketch and the expressive drawing ability of grade X students of SMA Bangun Insan Mandiri Medan.ABSTRAK Penelitian ini bertujuan untuk membuktikan ada tidaknya hubungan yang signifikan, besarnya kontribusi, dan untuk melihat besar kecilnya hubungan antara kemampuan menggambar bentuk dan sketsa dengan kemampuan menggambar ekspresif pada siswa kelas X SMA Bangun Insan Mandiri Medan. Metode yang digunakan dalam penelitian ini adalah penelitian korelasional, yaitu untuk melihat hubungan antara dua variabel bebas dengan variabel terikat. Populasi dalam penelitian ini adalah siswa kelas X SMA Bina Insam Mandiri Medan Tahun Pelajaran 2019/2020 yang berjumlah 32 siswa. Berdasarkan hasil penelitian dan pembahasan dapat disimpulkan bahwa terdapat hubungan antara kemampuan menggambar bentuk dan menggambar sketsa secara simultan terhadap kemampuan menggambar ekspresif siswa kelas X SMA Bangun Insan Mandiri Medan. Secara parsial terdapat hubungan antara kemampuan menggambar bentuk dengan kemampuan menggambar ekspresif siswa kelas X SMA Bangun Insan Mandiri Medan. Kata Kunci: Draw Shapes; Sketches; Expressive